Rheumatoid arthritis and genetic markers in Syrian and French populations: different effect of the shared epitope. Issue 2 (26th October 2006) - Kazkaz, Leyla; Marotte, Hubert; Hamwi, Mayassa; Angélique Cazalis, Marie; Roy, Pascal; Mougin, Bruno; Miossec, Pierre
Abstract : Objective: To investigate whether ethnic differences exist in the effect of the shared epitope and selected cytokine gene polymorphisms on the susceptibility and severity of rheumatoid arthritis in Syria (Damascus) and France (Rhône-Alpes area). Methods: 156 patients with rheumatoid arthritis and 120 healthy controls from Syria were compared with 512 patients with rheumatoid arthritis and 471 healthy controls from France. Shared epitope status, cytokine gene polymorphisms interleukin (IL)-1B +3954, IL-1RN +2018 and tumour necrosis factor α promoter (−238 and −308) were analysed by enzyme-linked oligosorbent assay. Joint destruction was defined by a right wrist Larsen score ⩾2. Odds ratios (ORs) were calculated. Results: In both countries, a dose effect was observed between the shared epitope copy number and rheumatoid arthritis (Syria: OR 1 v 0 copies = 1.6, p = NS; OR 2 v 0 = 15.3, p<0.01; and France: OR 1 v 0 = 2.3, p<0.001; OR 2 v 0 = 7.2, p<0.001). A dose effect was also observed between the shared epitope copy number and joint destruction in Syria (OR 1 v 0 = 2.2, p = NS; OR 2 v 0 = 9.9, p<0.01) and France (OR 1 v 0 = 1.8, p<0.01; OR 2 v 0 = 4.8, p = 0.001). The dose effect of the shared epitope was greater in Syria than in France. Only the −238 tumour necrosis factor α polymorphism was associated with joint destruction in the Syrian population (p<0.05). However, after adjustment for age, sex, disease duration and rheumatoid factor for severity, this association disappeared. Conclusion: The frequency of the shared epitope was increased in the French population with rheumatoid arthritis and in controls, but the association between the shared epitope and joint destruction was more pronounced in the Syrian population, with an OR of almost 10 for the homozygotes.